2011
DOI: 10.1055/s-0031-1283184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acute Eccentric Exercise on the H:Q Ratio

Abstract: The purpose of the present study was to examine the effects of an acute bout of eccentric exercise on maximal isokinetic concentric peak torque (PT) of the leg flexors and extensors and the hamstrings-to-quadriceps (H:Q) strength ratio. Sixteen male (mean±SD: age=20.9±2 years; stature=177.0±4.4 cm; mass=76.8±10.0 kg) volunteers performed maximal, concentric isokinetic leg extension and flexion muscle actions at 60°·sec - 1 before and after (24-72 h) a bout of eccentric exercise. The eccentric exercise protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The unique responses in LE and LF strength resulted in a significant decrease in the H/Q ratio at both W15 and W30 of the academy when compared with baseline. Previous studies have suggested that a reduction in the H/Q ratio is a risk factor for hamstring and/or knee injury (20–22). The decrease in H/Q ratio at W30 of the academy in the present study may increase the risk of lower body musculoskeletal injuries in recruits as they transition into their probationary period as active-duty career firefighters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unique responses in LE and LF strength resulted in a significant decrease in the H/Q ratio at both W15 and W30 of the academy when compared with baseline. Previous studies have suggested that a reduction in the H/Q ratio is a risk factor for hamstring and/or knee injury (20–22). The decrease in H/Q ratio at W30 of the academy in the present study may increase the risk of lower body musculoskeletal injuries in recruits as they transition into their probationary period as active-duty career firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…The order of MVC was randomized before data collection. In addition, the H/Q ratio was also determined by dividing leg flexion (LF) MVC PT by leg extension (LE) MVC PT (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common isokinetic testing protocol for assessing PT values on an isokinetic dynamometer uses a single set model where the subjects are typically warmed-up with concentric isokinetic contractions (often following a general warm-up), briefly familiarized and then perform 1 set (per velocity) of usually ~3–5 repetitions [ 2 , 6 , 13 , 16 , 17 , 18 , 19 ]. Although some studies have used a multiple set [ 4 , 20 ] testing scheme, it remains unknown as to whether the best testing protocol for determining one’s PT performance may involve more than a single set as a potential means to optimize best performance detection and reliability. Indeed, there is some evidence that a multiple-trial muscle function test protocol may be optimal.…”
Section: Introductionmentioning
confidence: 99%
“…To further complicate the analysis, the best method for determining or selecting the PT value that best represents the person’s maximal strength is also varied and has not been well studied. For instance, PT has been reported as the single highest value of all sets/reps [ 4 , 16 , 17 , 18 , 19 , 20 ], as the mean of all values [ 13 , 17 ], and as some variation of dropping one or more values and averaging the rest of the values [ 2 , 22 , 23 ]. No consensus to date has been provided that offers investigators the most objectively superior procedures for determining how to design an optimal testing protocol and select the best PT value out of the multi-value output.…”
Section: Introductionmentioning
confidence: 99%